2022
DOI: 10.1088/1755-1315/1026/1/012004
|View full text |Cite
|
Sign up to set email alerts
|

Study of Saudi Arabian Manufacturing and Service Organization Sustainability and Future Research Directions

Abstract: Currently, organizations face a range of dynamic challenges to maintain long-term market sustainability. Examples of these challenges are developing and improving their product and or service quality, increasing operational efficiency, complying with safety regulations, enhancing the triple bottom line of agility in manufacturing products and satisfying customer demand. Saudi Arabia has a vision for 2030 where sustainability is one of the corner stones. Here the objective is to explore sustainability awareness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Moreover, Ref. [70] discovered the awareness of sustainability using ESG criteria in Saudi organizations and their obligation to sustainability by reducing the risks of the organization's sustainability. Ref.…”
Section: Literature Review and The Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Ref. [70] discovered the awareness of sustainability using ESG criteria in Saudi organizations and their obligation to sustainability by reducing the risks of the organization's sustainability. Ref.…”
Section: Literature Review and The Theoretical Frameworkmentioning
confidence: 99%
“…Responses to the interview's questions showed a lack of awareness of ESG sustainability reporting, indicating a negative tendency towards the awareness of Saudi SMEs and ESG sustainability reporting [68,70]. Hence, most of the participants do not have any understanding of the sustainability concept.…”
Section: Awareness Of Sustainabilitymentioning
confidence: 99%
“…Another issue is how to combine different sub-criteria into a constructed index, enabling the efficient assessment of a company's sustainability and benchmarking. Another issue is that the methodologies for combining criteria are neither well established nor available for all sustainability aspects [1]. Moreover, there are no studies found in the literature assessing the sustainability of Saudi manufacturing organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, to establish a baseline for any organization's sustainable performance and to conduct competitive benchmarking, sustainability indexing is a critical competitive factor if it is conducted in the correct way. From the published literature [1], it is evident that researchers and practitioners have implemented sustainability evaluations in different sectors. However, the process of sustainability evaluation is still in its growing stage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation